Neurocognitive Behavior Analysis of Sexting Phenomenon in Young Adults - Gkintoni, Evgenia; Halkiopoulos, Constantinos; Antonopoulou, Hera; Koutsopoulou, Ioanna (Technium Social Sciences Journal, 2021)
Recent advancements in information and communication technology (ICT) and the growing use of technological equipment by young adults, combined with unrestricted access to the Internet and social media and the unrestricted use of smartphones and computers, have resulted in the emergence of social phenomena such as sexting. This article serves two purposes: To capture the phenomenon of sexting to investigate young adults' perceptions of sexting and the frequency with which social media users exchange sexual messages via a self-report questionnaire and to describe the behavioral profile of social media users network users via a cognitive decision-making detection test. Data were collected and analyzed using descriptive statistical analysis methods from a sample of young adults, students, and social network users (N = 377, Age: 18-39 years). The findings indicated that the sexting phenomenon is gaining traction among young adults, based on data processing and analysis from the administration of the reference questionnaire. Simultaneously, it appears to be related to participants' behavioral profiles in the cognitive dimension of decision-making. The current study's findings, which are being piloted, may aid in developing broad conclusions that can be accepted and affect policy and decision-making in the disciplines of clinical psychology, and cognitive neuroscience and education. In summary, sexting poses numerous risks to young adults in Greece and must be addressed more effectively in the interests of stakeholders and the larger community. Additionally, lawmakers, legislators, and authorities should take steps to safeguard children, adolescents, and young people who are heavily interested in social media and have integrated it into their daily life.